Functional role(s) of phagosomal Rab GTPases - Gutierrez, Maximiliano Gabriel (Landes Bioscience, 2013)
Rab GTPases are at the central node of the machinery that regulates trafficking of organelles, including phagosomes. Thanks to the unique combination of high quality phagosome purification with highly sensitive proteomic studies, the network of Rab proteins that are dynamically associated with phagosomes during the process of maturation of this organelle is relatively well known. Whereas the phagosomal functions of many of the Rab proteins associated with phagosomes are characterized, the role(s) of most of these trafficking regulators remains to be identified. In some cases, even when the function in the context of phagosome biology is described, phagosomal Rab proteins seem to have similar roles. This review summarizes the current knowledge about the identity and function of phagosomal Rab GTPases, with a particular emphasis on new evidence that clarify these seemingly overlapping Rab functions during phagosome maturation.